Translation: A commitment to transdisciplinary exploration (translation. a transdisciplinary journal, 2021)
This is translation's first regular issue. After an encouraging start with the inaugural issue chat was sent out to readers in numerous countries around the globe, and after significant positive feedback, we look forward to this challenge to create a fresh, lively, and ongoing dialogue with our readers and authors-in both the journal's paper and online versions.